Effect of hydraulic retention time on performances of gravity-driven membrane (GDM) reactor for seawater pretreatment - Lee, Seonki (2023)
This study aims to illustrate the effect of hydraulic retention time (HRT) on reactor performance and biofilm characteristics in the gravity-driven membrane (GDM) reactor pretreating seawater. Three GDM reactors were operated in parallel for ~62 days under HRTs of 22 h, 54 h, and 102 h, respectively. The results indicated that the GDM reactors at HRTs of 22 h and 102 h had relatively higher permeate flux and superior permeate quality (especially assimilable organic carbon, AOC) compared to that at HRT of 54 h. Extending HRT benefited to reduce irreversible fouling, but cake layer fouling was maximized at HRT of 54 h. As different HRTs led to significantly dissimilar microbial community structure and cake layer composition, such higher cake layer resistance at HRT of 54 h was attributed to homogenous nature of the biofilm, which contained greater amount of organics and less abundance of Nematoda (dominant predator). Lastly, as increasing ~5-time of HRT (from 22 h to 102 h) improved ~1.5 of permeate flux, a shorter HRT of 22 h was preferable for the GDM reactor in pretreating seawater with regard to treatment productivity and footprint.